2010
DOI: 10.1016/j.ejvs.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Fenestrated Stent Grafting for Short-necked and Juxtarenal Abdominal Aortic Aneurysm: An 8-Year Single-centre Experience

Abstract: Fenestrated stent grafting for short-necked and juxtarenal abdominal aortic aneurysm appears safe and effective on the longer term. Renal function deterioration, however, is a major concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
252
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(263 citation statements)
references
References 21 publications
8
252
0
3
Order By: Relevance
“…23) The placement of our brachio-femoral shunt is technically easier than from Europe and United States have indicated good results of FEVAR using a Cook fenestrated stent-graft for JAA at both initial and mid-term follow-ups. 5,19,20) A recent literature review indicated that FEVAR can be performed with a 30-day mortality rate of 2.1%, 21) which is comparable to the rate for standard EVAR. Although the use of the fenestrated stent-graft has been increasing in western countries after its use was approved by certain governments, it is uncertain when the Japanese government will approve the device with health insurance coverage.…”
Section: Discussionmentioning
confidence: 95%
“…23) The placement of our brachio-femoral shunt is technically easier than from Europe and United States have indicated good results of FEVAR using a Cook fenestrated stent-graft for JAA at both initial and mid-term follow-ups. 5,19,20) A recent literature review indicated that FEVAR can be performed with a 30-day mortality rate of 2.1%, 21) which is comparable to the rate for standard EVAR. Although the use of the fenestrated stent-graft has been increasing in western countries after its use was approved by certain governments, it is uncertain when the Japanese government will approve the device with health insurance coverage.…”
Section: Discussionmentioning
confidence: 95%
“…2). Initial experiences with these devices have shown that total endovascular repair is effective and may reduce morbidity rates in patients with arch, thoracoabdominal, pararenal and juxtarenal aneurysms [14][15][16][17][18][19][20][21]. Treatment of chronic type B aortic dissection with the use of fenestrated devices has also been reported with good preliminary results [22,23].…”
Section: Fenestrated and Branched Stent Graftsmentioning
confidence: 98%
“…Evolution of stent graft design including suprarenal fixation 20 and renal and mesenteric fenestration 21 are examples. Adjunctive neck measures, eg endostapling, 22,23 proximal fibrin glue embolisation, 24 open aortic neck banding, 25 and proximal covered cuff extension 10 may be used in cases of perioperative type 1a endoleak following EVAR.…”
Section: Discussionmentioning
confidence: 99%